1999
DOI: 10.1063/1.479620
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of current density functionals for the calculation of electric field gradients: A comparison with ab initio methods for HCl and CuCl

Abstract: The performance of current density functionals is analyzed in detail for the electric field gradients (EFG) of hydrogen chloride and copper chloride by comparison with ab initio methods and available experimental data. The range of density functionals applied shows good agreement with coupled cluster H and Cl field gradients for HCl, as has been demonstrated previously for other main-group element containing compounds. However, the performance of most density functionals is very poor for the Cu EFG in CuCl (EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
83
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 73 publications
9
83
2
Order By: Relevance
“…On the other hand, the calculated EFGs at the halogen centers in the Cu and Ag halides are not in good agreement with experiment, which confirms the results previously found in Ref. 18 for CuCl. Since the discrepancy cannot be due to ''technical'' problems ͑ZORA, basis sets͒ it is to be attributed to deficiency of the used density functional: LDA plus gradient corrections due to Becke ͑Becke88͒ 19 and Perdew.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…On the other hand, the calculated EFGs at the halogen centers in the Cu and Ag halides are not in good agreement with experiment, which confirms the results previously found in Ref. 18 for CuCl. Since the discrepancy cannot be due to ''technical'' problems ͑ZORA, basis sets͒ it is to be attributed to deficiency of the used density functional: LDA plus gradient corrections due to Becke ͑Becke88͒ 19 and Perdew.…”
Section: Discussionsupporting
confidence: 75%
“…For these molecules the used density functional fails to describe the electric field gradient with sufficient accuracy. Schwerdtfeger et al 18 showed that many of the presently used functionals, with the exception of some hybrid functionals, give poor results for CuCl. They showed that the results are even worse for the calculation of the EFG at the copper nucleus.…”
Section: Electric Field Gradients In Diatomic Halidesmentioning
confidence: 99%
“…If we accept the coupled-cluster result as the most accurate value, the hybrid GGA functionals perform well for Fe(CO) 5 , while the non-hybrid GGA functionals are preferred for Fe(C 5 H 5 ) 2 . We note that for CuCl the BHH functionals gave the best description [19]. This is clearly not a satisfying situation.…”
mentioning
confidence: 90%
“…The use of the density functional theory for the calculation of EFGs in transition metals is questionable. Recent calculations on CuF showed a variation of the Cu EFG ranging from +0.50 au for the local density approximation (LDA), and +0.44 au at the generalized gradient approximation (GGA) level (BPW91) to +0.07 au at the hybrid level (B3PW91) [19,20], as compared to the experimental value of −0.31(2) au [21]. In contrast, relativistic ab initio coupled-cluster calculations give −0.34 au [19], in perfect agreement with the experimental result.…”
mentioning
confidence: 99%
See 1 more Smart Citation